The Role of Nato in Enhancing Ukraine’s Cybersecurity during Times of Conflict - Triwahyuni, Dewi; Valentino, Leonardo; Amada, Nenden Nurmutiasari; Bustami, Harya (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This study aims to analyze the impact of NATO support on Ukraine which is in a conflict situation with Russia. Ukraine has taken a step forward to strengthen its ties with NATO by signing an agreement to formalize its participation in the security alliance’s Joint Center for Advanced Technologies in Cyber Defense (CCDCOE). This study will discover how this action will affect the tensions in the Cyber Security System between Ukraine and Russia. In order to find the answer, it is necessary to identify the motives by using qualitative research design through secondary sources in the form of official state documents and secondary sources in the form of journals, dissertations and related research. The result of this study conluded NATO’s involvement in the cyber war between UkraineRussia is quite substantial and greatly influenced the course of the war, this is what motivated the researcher to conduct further studies and see what influences were given., regardless of the difficult to collect the information. This study might help us understand the situation of Cyber Conflict between Ukraine-Russia and predicts the potential consequences from this action, and hopefully give us more informations to analyze and evaluate to find the best solution of this existing conflict.